Pola Asuh Orang Tua Terhadap Tingkat Kemandirian Anak Retardasi Mental Di Sekolah Luar Biasa Negeri Sukamaju Simpang Propau Kabupaten Lampung Utara - Mariani, Rina (Jurnal Kesehatan Metro Sai Wawai, 2016)
Parenting scheme that choosen by parents to guide and educate mental retardation child different with normal child. One of purpose from parenting scheme by parents is to make child become helpful for others and his self. Presurvey that has done in SLBN sukamaju in febuary of 2015, from 7 parents that given question, 4 (57,14%) parents say their child still need help when take a bath, fed when eat, need help when wear clothes, when play need family accompanion. While 3 (42,86%) parents say their child can take a bath, eat, wearing clothes by his self, and only when play their child need to be controlled. Researcher want to know Is there a correlation between parenting scheme and mental retardation child autonomy in SLBN sukamaju propau north lampung in 2015. Design of this study is quantitative analytical and use cross sectional approach. Populations of this study are all of parents that have retardation mental chils that have total 32 parents. Sample and sampling technique are total population. Study variable are independent variable is parenting scheme and dependent variable is child’s autonomy level. Data analysis is univariat analysis and bivariat analysis through chi square test with α = 0,05. Result of the study get from 32 respondents, 7 (21,9%) have otority parenting scheme, and autonomy child from mental retardation child are 12 (37,5%). The bivariat result get nothing correlation between parenting scheme towards retardation mental child autonomy with p value 0,683 (p>0,05). Suggestion for SLB school worker to make prenting school program to optimize parenting scheme towards menta; retardation child autonomy.